Oral Health Status of the Elderly at Tonga, West Region, Cameroon - Yotat Michele Lolita; Agbor Ashu Michael; Ntumba Hubert; Djachechi Florence; Bolenge Jacques (International Journal of Dentistry)
Objectives. The aim of this study was to determine the oral health status of elderly persons in Tonga, West Region of Cameroon. Methodology. This is a cross-sectional study of persons of at least 65 years, living in Tonga village, West Region of Cameroon. Results. A total of 183 persons aged between 65 and 94 years, mean age of 73 years ±7 s.d., 83 (45,4%) males, and 100 (54,6%) females participated in the study. The most represented age range was 65–74 years (60.1%); 86 (47.3%) and elders above 65 constituted 1.8% of the total population. More than a third 117 (41.4%) had visible dental plaque, 117 (48,6%) had periodontal pockets >4 mm, 153 (54,1%) had teeth with total crown destruction, 70 (38.3%) had not lost a tooth, 23 (12.6%) had lost 1 tooth, 19 (10.4%) have lost at least 2 teeth, 100 (55.7%) were partially edentulous at the maxilla and 98 (53.6%) at the mandible, 2 (1.1%) were completely edentulous at the maxilla and 3 (1.6%) at the mandible, and 3.8% had removable dentures. The mean DMF index was 6.11 and 69.4% had dental caries. Risk factors to dental caries were toothbrushing and tobacco consumption while dental plaque was associated to pocket depth of 4–6 mm. Barriers to oral health care included ignorance 47 (25.7%), financial difficulties 124 (67.8%), and distance to the nearest clinic 12 (6.5%). Conclusion. The oral status of the elderly was generally poor.